PENGARUH ELEARNING TERHADAP PEMAHAMAN DASAR STATISTIKA MAHASISWA TARBIYAH - Riska Yulianti; Prihaten Maskhuliah; Suminarti Hutajulu (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
This is a quantitative research that aims to determine the effect of elearning on the basic understanding of statistics in Tarbiyah students. The population of this research is all students of Tarbiyah IAIN Fattahul Muluk Papua who contracted statistics courses in the even semester. Samples were taken with a purposive sampling technique of 45 Tarbiyah students from the Islamic Education Study Program, Mathematic Education Study Program and English Education Study Program. The instrument used was a Likert scale questionnaire. The data obtained were analyzed with descriptive statistics and parametric statistics. The results showed that: (1) most students can access and operate certain applications that are used in elearning as a substitute for direct learning and have a good basic understanding of statistics; (2) there is an influence of elearning on the basic understanding of statistics in Tarbiyah students; (3) the magnitude of the effect of elearning on basic understanding of statistics in Tarbiyah students is 0.177 or 17.7%.